'Getting used to' hearing aids from the perspective of adult hearing-aid users. (December 2014) - Dawes, Piers; Maslin, Michael; Munro, Kevin J.
Abstract Objective: To describe getting used to hearing aids from the perspective of adult hearing-aid users. Design: Three focus group discussions were carried out. A topic guide and discussion exercises were used to elicit views on getting used to hearing aids. Discussion was audio recorded, transcribed verbatim, and subjected to qualitative content analysis. Study sample: Adult hearing aid users (n = 16). Results: Participants described getting used to hearing aids as a multi-factorial process which included adjusting to altered sensory input, practical matters such as cleaning and maintenance, and managing the psychosocial impact of hearing-aid use, such as on self-image. Users reported a process of discovering benefits and limitations of hearing aids leading to individual patterns of use that was relatively independent of input from audiologists. Conclusions: Getting used to hearing aids is a challenging multi-factorial process with both psychosocial and practical difficulties besides demands of adjusting to hearing-aid input.